Functional Characteristic of Analog Rice Made From Taro Kimpul Flour (Xhantosoma sagitifolium) - Santi Noviasari; Permata Salsa Assyifa; Ismail Sulaiman (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2022)
Abstract: Analog rice is artificial rice made from carbohydrate sources to resemble rice. Taro kimpul is one of Indonesia's local foods rich in carbohydrates that have not been widely used and have functional properties to be used as a raw material for analog rice. In this study, the manufacture of analog rice also used functional ingredients (beets and dragon fruit peels) containing phytochemical beneficial compounds and binders (carboxymethyl cellulose/CMC and carrageenan). This research aimed to determine the functional characteristics of analog rice and was expected to produce analog rice with a low-calorie value. The research was conducted in two stages: analog rice was made with four formulations; and an analysis of the functional characteristics of analog rice was conducted. This research was done with descriptive analysis so that it could describe the effect of adding functional ingredients and binders to the characteristics of analog rice. Based on the decision-making method, the best treatment in this study was taro analog rice F1 with the use of 2% carrageenan and 32% beetroot. The functional characteristics of taro analog rice F1 are as follows: crude fiber 2.13%, calories 112.29 kcal/100g, total phenol 0.51 mg GAE/g, anthocyanin 56.77mg/100g, and antioxidant activity of 74.92%. The analog rice obtained had higher antioxidant activity, total phenol, anthocyanin, and lower calorific value compared to polished rice.Abstrak: Beras analog adalah beras tiruan yang dibuat dari sumber karbohidrat menyerupai beras. Talas kimpul merupakan salah satu pangan lokal Indonesia yang kaya akan karbohidrat yang belum banyak dimanfaatkan dan memiliki sifat fungsional yang berpotensi digunakan sebagai bahan baku beras analog. Dalam penelitian ini, pembuatan beras analog menggunakan bahan-bahan fungsional (bit dan kulit buah naga) yang mengandung senyawa fungsional dan bahan pengikat (CMC dan karagenan). Penelitian ini bertujuan untuk mengetahui karakteristik fungsional beras analog talas dan diharapkan dapat menghasilkan beras analog dengan nilai kalori yang rendah. Penelitian telah dilakukan dengan dua tahap: pembuatan beras analog empat formulasi; dan analisis karakteristik fungsional pada beras analog. Penelitian ini dianalisis secara deskriptif sehingga menjelaskan pengaruh penambahan bahan fungsional dan pengikat terhadap karakteristik beras analog. Berdasarkan metode pengambilan keputusan perlakuan terbaik dalam penelitian ini adalah beras analog talas F1 dengan penggunaan 2% karagenan dan bit 32% dengan karakteristik sebagai berikut: serat kasar 2,13%, kalori 112,29 kkal/100g, total fenol 0,51 mg GAE/g, antosianin 56,77mg/100g dan aktivitas antioksidan 74,92%. Beras analog yang dihasilkan memiliki aktivitas antioksidan, total fenol, antosianin yang lebih tinggi dan nilai kalori yang lebih rendah dibandingkan dengan beras sosoh.